The Influence Of Fundamental Factors On Stock Price In Listed Agricultural Sector Companies On The Indonesian Stock Exchange - lia, Nur April (Politeknik Negeri Bengkalis, 2023)
This research was conducted at the Indonesia Stock Exchange. This research is classified as descriptive and associative because this research determines the causal relationship between the independent variables and the dependent variable. The population in this study are all agricultural sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Sampling in this study is by Purposive Sampling, namely the sampling method using criteria. The samples in this study amounted to 16 companies with a total sample of 80. The purpose of this study was to determine the effect of Current Ratio, Return On Assets, Earning Per Share, Debt To Equity Ratio, Inventory Turnover on stock prices of agricultural sector companies listed on the Indonesia Stock Exchange for the period 2017-2021.